An Analysis of Motivational Factors Affecting Employee Performance - Dangol, Pooja (Journal of Business and Social Sciences Research, 2020)
It is essential for organisations to pay attention to the well-being of their employees. The organisation should create a workplace that is engaging and motivating, where employees want to stay, grow and contribute their skills, knowledge and expertise. The present research study aims to investigate motivational factors (goal-setting, monetary rewards, recognition programmes and training) that aids in upsurge of employee performance. The study adopted a descriptive research design. The population consists of 130 employees of 30 companies of Nepal. Data was collected using structured questionnaires. Statistical tools such as frequency distribution, mean score, correlation analysis and regression analysis were used to analyse data and were presented using tables. The results reveal that there exists a positive and significant relationship between goal-setting, recognition programmes and training on employee performance. The findings suggest that employees value their own personal growth. Organisations should come up with personal development programmes to improve performance. The study results are expected to offer inputs in assessing and implementing motivational factors in organisations.